Pengembangan Video Pembelajaran Desain Interior Kelas X Jurusan Gambar di SMKN Bakalang - Nuraini Ela; Isma Nastiti Maharani; Dadan Rahmat (Peneliti.net, 2022)
The research that was conducted at the Akanang Vocational High School was because the school lacked learning media that could support learning, the main purpose of the research was to produce a media product in the form of a learning video that became a student learning companion. research and development Research and Development (R&D) is a research method used to produce certain products and test the effectiveness of these products (Sugiyono, 2014). Research and development is used for the development and verification process of research products (Borg and Gall 1983). The results of research and development are developing and producing products in the form of learning videos, as well as determining the feasibility of the products being developed, which produces media in the form of learning videos Mp4 files, with material experts, media experts, students X images as users. The final result of the developed product assessment obtained a score of 58 percentage 95% with the category